2010
DOI: 10.1021/jp108759b
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Dioxide Adsorption on TiO2 Nanoparticles: Influence of Particle Size, Coadsorbates, Sample Pretreatment, and Light on Surface Speciation and Surface Coverage

Abstract: The adsorption of sulfur dioxide (SO 2 ) on titanium dioxide (TiO 2 ) nanoparticle surfaces at 296 K under a wide range of conditions has been investigated. X-ray photoelectron spectroscopy is used to investigate the surface speciation and surface coverage of sulfur-containing products on ca. 4 nm TiO 2 anatase particles that remain on the surface following adsorption of SO 2 . The effects of various environmental conditions of relative humidity, molecular oxygen, and broadband UV/vis irradiation as well as sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 61 publications
4
101
1
2
Order By: Relevance
“…It was reported in the research of Li et al [25] that NO was mainly adsorbed to the hydroxyl groups on the surface of photocatalyst due to strong bonding NO to TiO 2 induced by charge transfer. However, the hydroxyl groups are also important for SO 2 chemisorbed on TiO 2 in the form of sulfite [26]. Therefore, competition for the surface hydroxyl groups between SO 2 and NO is inevitable while introducing SO 2 and NO into simulated flue gas simultaneously.…”
Section: Photocatalytic Desulfurizationmentioning
confidence: 99%
“…It was reported in the research of Li et al [25] that NO was mainly adsorbed to the hydroxyl groups on the surface of photocatalyst due to strong bonding NO to TiO 2 induced by charge transfer. However, the hydroxyl groups are also important for SO 2 chemisorbed on TiO 2 in the form of sulfite [26]. Therefore, competition for the surface hydroxyl groups between SO 2 and NO is inevitable while introducing SO 2 and NO into simulated flue gas simultaneously.…”
Section: Photocatalytic Desulfurizationmentioning
confidence: 99%
“…There was also a difference in the size of the response since humidity increased the size of the response to SO 2 . Most likely this was caused by a surface reaction between SO 2 and water forming HSO 3 - [30,31], which might adsorb on the sensor surface and thereby contribute to the response of by the sensor. In Figure 10(b) shows a close up of the sensor signal.…”
Section: Influence Of Humiditymentioning
confidence: 99%
“…During advection, mineral dust particles interact with sulfur dioxide (SO 2 ) and other atmospheric trace gases. Current knowledge shows that sulfur dioxide adsorbs onto many of the components of mineral dust as adsorbed sulfite, which can be oxidized to sulfate (3), for example, by ozone (4), by surface defect sites, or by photooxidation (5)(6)(7)(8). These previous studies (and references therein) clearly demonstrated that particulate sulfate is the end product of the SO 2 chemistry on dust surfaces (9).…”
mentioning
confidence: 92%